KONTRIBUSI SOSIAL: SOSIALISASI EDUKASI TBC GUNA MENINGKATKAN KUALITAS HIDUP MASYARAKAT - Hapsari, RR Prima Dita; Sutrisno, Gono; Sari, Santi Purnama; Umiyati, Hesti (Jurnal Berdaya Mandiri, 2025)
Indonesia holds the second-highest number of tuberculosis cases globally. This poses a significant challenge to the goal of eliminating the disease by 2030. In response, this community service initiative was carried out to support the government's target. The outreach aimed to provide a platform for health education, specifically on tuberculosis. The activity was conducted in Koang Jaya Village, Karawaci District, Tangerang City, an area with a notably high number of tuberculosis cases. The public's enthusiasm and participation in this educational event were considerable. Ultimately, it is hoped that an increase in public knowledge will help mitigate the spread of tuberculosis, thus contributing to the government's objective of minimizing the disease's prevalence by 2030. Keywords: Education; quality of life; social contribution; tuberculosis